Developing Socio-Cultural Competence through English Songs in Foreign Language Teaching - Ablaeva Zhuldyz Muratkyzy (Research Retrieval and Academic Letters, 2023)
The topic "Developing Socio-Cultural Competence through English Songs in Foreign Language Teaching" addresses issues concerning the understanding and development of intercultural aspects in relation to teaching the English language. The research highlights situations and methods that educators can employ to broaden students' perspectives and engage them in the process of learning English through songs.